A test method for white EVA photovoltaic film overflow and wrinkles

By breaking the cell and laminating small-sized components, the white EVA film is solved and the white EVA film is overflowing and wrinkled during the photovoltaic module packaging process, achieving cost saving and improving the performance of photovoltaic modules.

CN119757361APending Publication Date: 2025-04-04ZHEJIANG FUNCTIONAL MEMBRANE MATERIAL INNOVATION CENT CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411906783.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The common whitening and wrinkle problems of existing white EVA films in photovoltaic module packaging have affected the performance, appearance and long-term stability of photovoltaic modules. The existing testing methods are time-consuming, labor-intensive and consumables, increasing production costs.

Method used

By breaking the cell and laminating small-sized components for testing, superimposed samples of transparent adhesive film, white adhesive film, glass and back plate were used to heat and laminate under vacuum to observe the overflow and wrinkle of the laminate.

Benefits of technology

This method is simple to operate, saves materials and short time, and can effectively identify and evaluate the whitening and wrinkle problems of white EVA film, reduce production costs, and improve the performance and market competitiveness of photovoltaic modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005204563910000091
    Figure BDA0005204563910000091
  • Figure HDA0005204563920000011
    Figure HDA0005204563920000011
  • Figure HDA0005204563920000012
    Figure HDA0005204563920000012
Patent Text Reader

Abstract

A photovoltaic film overflow and wrinkle test method includes selecting a transparent film, a white film, a glass and a back plate; selecting a square battery cell, knocking the center of the battery cell to break it; stacking the glass, the transparent film, the battery cell fragments, the white film and the back plate in sequence and fixing them; heating and laminating; observing the overflow and wrinkles of the laminate. The method is simple to operate, saves materials and has a short operation time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar encapsulation films, in particular to a method for testing white overflow and wrinkles of a white EVA photovoltaic film. Background Art

[0002] White EVA film plays an extremely important role in the encapsulation process of photovoltaic modules. It not only improves the photoelectric performance of photovoltaic modules and protects the cells, but also provides structural strength, weather resistance and thermal stability, extending the service life of photovoltaic modules. The excellent properties of white film make it an indispensable core material in the encapsulation of photovoltaic modules, which is of vital importance to improving the overall performance and market competitiveness of photovoltaic modules. In addition, white film also brings better appearance to photovoltaic modules and increases the market value of products. Against the background of the continuous development of photovoltaic technology, the innovation and optimization of white film will continue to promote the progress of the photovoltaic industry. In the production process of photovoltaic modules, white EVA film overflow and wrinkles are common quality problems, which will affect the performance, appearance and long-term stability of photovoltaic modules.

[0003] The testing of whitening and wrinkles when using white EVA film is a very necessary and important link in the production process of modules. By detecting whitening and wrinkles, defects that may reduce the efficiency of photovoltaic modules can be effectively identified, problems can be discovered in advance and corrected, so as to ensure that the photovoltaic performance of photovoltaic modules reaches the expected level. By detecting whitening and wrinkles, the quality of the film can be evaluated to ensure that its mechanical properties in photovoltaic modules meet the standards, thereby extending the service life of photovoltaic modules and reducing failures caused by structural problems. It can also ensure that the appearance quality of photovoltaic modules meets market standards, thereby improving the market competitiveness of products. Beautiful modules often gain more favor from consumers and promote sales and market share growth. The early detection of whitening and wrinkles in the production of photovoltaic modules as a quality control link can ensure product quality consistency, reduce losses caused by quality problems, improve production efficiency and reduce costs. In addition, these tests help to evaluate the long-term stability of photovoltaic modules, ensure that they maintain efficient operation in long-term use, meet the service life requirements of more than 20 years, and ensure that the products meet international standards and certification requirements, pass third-party testing smoothly, and improve product qualification rate and market acceptance.

[0004] At present, the early detection and verification of the overflow and wrinkle problems of white EVA film products by film manufacturers and the early detection and verification of the overflow and wrinkle problems of single-glass modules using white film by module manufacturers generally use the standard large module template lamination of the manufacturer's shipped products for detection. This method usually requires the number of laminated modules to be more than thousands of pieces, which consumes a lot of manpower, material resources and materials, and virtually increases the cost of the company's product production and operation. The present invention will provide a more cost-saving and easier to operate early detection method for overflow and wrinkle. Summary of the invention

[0005] In order to solve the problems of time-consuming, labor-consuming, and material-consuming problems of the existing white EVA film early overflow and wrinkle testing methods, the present invention provides a method for testing white EVA film early overflow and wrinkle. The film overflow and wrinkle testing method is simple to operate, saves materials, and has a short operation time.

[0006] The white film overflow and wrinkle testing method provided by the present invention is a testing method of breaking the battery sheet and laminating a small-sized component.

[0007] Whitening refers to excessive whitening on the surface or inside of the EVA film due to uneven film materials or process problems. This usually leads to defects in the appearance of photovoltaic modules, affecting the beauty of photovoltaic modules and the final market acceptance. It may also cause uneven light reflection and affect the photoelectric conversion efficiency of photovoltaic modules.

[0008] EVA film wrinkles refer to the phenomenon that the EVA film has surface folds or uneven surfaces due to stress, uneven heating or cooling, etc. during the photovoltaic module packaging process. These wrinkles will lead to poor adhesion between the film and the cell, which will affect the photovoltaic performance and reliability of the photovoltaic module. At the same time, wrinkles may cause poor contact between the film and other materials, increase the risk of moisture or air infiltration, and reduce the long-term stability of the photovoltaic module.

[0009] In order to solve the technical problems of white overflow and wrinkles, the present invention provides a method for testing white overflow and wrinkles of photovoltaic adhesive film, and the steps are as follows:

[0010] (1) Select transparent film, white film, glass and back panel;

[0011] (2) Select a square battery cell and hit the center of the cell to break it;

[0012] (3) Sample preparation: stack the glass, transparent film, cell fragments, white film and backplane in order from bottom to top and fix them;

[0013] (4) Heating lamination: heating lamination is performed under vacuum to obtain a laminate sample;

[0014] (5) Observe the test results: After the laminate cools down to room temperature, observe the whitening and wrinkles of the laminate.

[0015] Furthermore, the sizes of the transparent adhesive film, the white adhesive film, the glass and the back plate are m mm×n mm, and m and n are less than or equal to 1000, or 800, 500, 300, 200, and 100.

[0016] Furthermore, the size of the transparent adhesive film, the white adhesive film, the glass and the back panel is 200 mm×300 mm.

[0017] Furthermore, the transparent adhesive film is an EVA adhesive film or an EVT adhesive film.

[0018] Furthermore, the white film is a white EVA film, preferably a pure white EVA film or a co-extruded composite white EVA film.

[0019] Furthermore, the glass is ultra-clear embossed glass, preferably ultra-clear embossed tempered glass. The surface of the glass should be flat, clean and pollution-free.

[0020] Furthermore, the backplane is a white backplane, preferably a TPC backplane.

[0021] Furthermore, the surface of the defendant is smooth, without pollution, scratches, delamination or bubbles.

[0022] Furthermore, the size of the battery cell is M mm×M mm, where M is less than or equal to 800, or 600, 500, 400, 300, or 200.

[0023] Furthermore, the size of the battery cell is 166 mm×166 mm, 182 mm×182 mm or 210 mm×210 mm.

[0024] Furthermore, the cell is a TOPCon single-glass cell.

[0025] Furthermore, when the battery cell is knocked, dust-free paper is placed under the battery cell.

[0026] Furthermore, the battery cell is broken into four triangular fragments by being struck. Figure 1 shown.

[0027] Furthermore, during the sample preparation process in step (3), the sample is fixed using masking tape.

[0028] Furthermore, during the heating and laminating process in step (4), the vacuuming time is 50-1000 s, preferably 200 s, 300 s, 330 s, 400 s, 500 s, 600 s, 800 s, or 850 s.

[0029] Furthermore, during the heating and lamination process in step (4), the lamination time is 300-800 s, preferably 300 s, 340 s, 400 s, 500 s, 510 s, 600 s, or 700 s.

[0030] Furthermore, during the heating and lamination process in step (4), the lamination temperature is 100-180°C, preferably 100°C, 120°C, 140°C, or 160°C.

[0031] Furthermore, a hard material such as the end of a utility knife is used to strike the battery cell.

[0032] Furthermore, the distance between the edge of the battery cell and the edge of the glass is less than 50 mm, or is 40 mm, 30 mm, 20 mm, or 10 mm.

[0033] Furthermore, the number of the transparent adhesive film, the white adhesive film, the glass, the back plate, and the battery cell is one piece.

[0034] Furthermore, the method of the present invention comprises the following steps:

[0035] (1) Take a piece of transparent EVA film with a size of 200 mm × 300 mm, a piece of white EVA film with a size of 200 mm × 300 mm, a piece of ultra-clear embossed glass with a size of 200 mm × 300 mm with a flat surface, clean and pollution-free, and a piece of white backing board with a size of 200 mm × 300 mm with a flat surface, no pollution, no scratches, no delamination, and no bubbles.

[0036] (2) Take a TOPCon single-glass cell with a size of 166mm×166mm, 182mm×182mm or 210mm×210mm, place the cell on a clean, flat work surface, and place a layer of dust-free paper with a size of 300mm×300mm under the cell (the size of the dust-free paper must be larger than the size of the cell). Use the tail of a common utility knife on the market to gently tap the center of the cell to break the entire cell into four triangular fragments, such as Figure 1 shown.

[0037] (3) Sample preparation: Stack the glass, transparent EVA film 1, battery cell fragments, white EVA film 2, and backplane in this order from bottom to top, and then fix them with masking tape.

[0038] (4) Heating and laminating: Set the vacuuming time to 330 seconds, the laminating time to 510 seconds, and the laminating temperature to 140°C to obtain a laminate sample with no defects in appearance.

[0039] (5) Observation. After lamination, use high-temperature gloves to place the laminate in a ventilated place to cool the laminate to room temperature, and then observe the whitening and wrinkles of the laminate.

[0040] Furthermore, the transparent EVA film 1 is a transparent EVA, a type of EVT, and the white EVA film 2 is a pure white EVA film, a type of co-extruded composite white EVA film. The cutting size is 200mm×300mm.

[0041] Furthermore, the glass is ultra-clear embossed tempered glass with a size of 200mm×300mm.

[0042] Furthermore, the backplane is a white TPC backplane with a size of 200mm×300mm.

[0043] Further, the backplane, glass, and film are stacked in the order of glass, transparent EVA film 1, battery cell fragments, white EVA film 2, and backplane from bottom to top, where the embossed surface of the glass faces upward to contact the transparent EVA film 1, and the 200 mm long sides of the transparent EVA film 1 and the white EVA film 2 correspond to the 200 mm long sides of the glass and the backplane, as shown in FIG. Figure 2 Then use masking tape to secure the four corners of the laminate and the midpoints of the long sides of the laminate.

[0044] Furthermore, the distance between the edge of the cell fragment and the edge of the glass is 10 mm. Figure 2 shown.

[0045] Furthermore, the vacuuming time was set to 330 s, the lamination time to 510 s, and the lamination temperature to 140° C. for lamination.

[0046] Furthermore, when knocking the battery cell, in order to avoid irregular breakage of the battery cell, use a hard material such as the end of a utility knife to knock it, and the dust-free paper and work surface under the battery cell must be clean and flat.

[0047] Furthermore, in the test method, the back side of the battery cell fragments contacts the white EVA film during sample preparation.

[0048] The purpose of the present invention is to provide a more convenient, quick and material-saving method for testing white photovoltaic film overflow and wrinkles, and the test is completed by the above method.

[0049] Compared with the prior art, the white overflow and wrinkle testing method provided by the present invention has the following advantages:

[0050] (1) The present invention provides a method for testing white EVA photovoltaic film for whitening and wrinkles. Compared with the method currently used by film manufacturers and component manufacturers on the market to test whitening and wrinkles using large standard laminates, this method uses fewer cells, uses cell residues to increase cell utilization, reduces the use of consumables, and saves costs.

[0051] (2) The overflow and wrinkle testing method adopted by the present invention is more convenient to operate in the actual production and testing process. Since the sample size prepared by the method described in this patent is relatively small, multiple samples can be laminated at the same time, so the testing work is more efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 Schematic diagram of breaking the battery cell.

[0053] 1 is a utility knife, 2 is battery cell fragments, 3 is dust-free paper.

[0054] Figure 2 Schematic diagram of laminate stacking.

[0055] 1 is the patterned glass, 2 is the transparent film, 3 is the cell fragment, 4 is the white film, and 5 is the white backplane. The red line in the close-up indicates that the distance between the cell edge and the glass edge is 10mm.

[0056] Figure 3 Schematic diagram of the actual laminated sample.

[0057] Figure 4 A partial schematic diagram of the fold.

[0058] Figure 5 This is a partial schematic diagram of overflow. DETAILED DESCRIPTION

[0059] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the following will be combined with the preferred embodiments of the present invention and described in detail as follows:

[0060] like Figure 3 As shown, the embossed tempered glass is at the bottom, with a size of 200mm×300mm; the transparent EVA film 1 and the white EVA film 2 are in the middle, with a size of 200mm×300mm; the battery cell fragments are located between the film 1 and the film 2, and the distance between the edge of the battery cell and the edge of the film (glass) is 10mm; the upper layer is the backplane, with a size of 200mm×300mm, as shown in FIG. Figure 2 shown.

[0061] Comparative Example 1

[0062] Take a transparent EVA film of 1830mm×1020mm and a pre-crosslinked white EVA film, a piece of ultra-white embossed glass of 1830mm×1020mm with a flat surface, clean and pollution-free, and a white backplane of 1830mm×1020mm with a flat surface, no pollution, no scratches, no delamination, and no bubbles. Take several TOPCon single-glass cells of 182mm×182mm and laminate them according to the normal standard version of the module size designed by the module factory. The vacuum time is 330S, the lamination temperature is 140℃, and the lamination time is 510S. After the laminated components are cooled, observe the overflow and wrinkles. The number of laminated components is 1000.

[0063] Comparative Example 2

[0064] Take a transparent EVA film with a size of 2100mm×1050mm and a white composite co-extruded EVA film that has been pre-crosslinked, a piece of ultra-white embossed glass with a size of 2100mm×1050mm with a flat surface, clean and pollution-free, and a white backplane with a size of 2100mm×1050mm with a flat surface, no pollution, no scratches, no delamination, and no bubbles. Use high-energy electron beam irradiation equipment to irradiate the white composite co-extruded EVA film under certain parameters. Take several TOPCon single-glass cells with a size of 210mm×210mm, and laminate them according to the normal standard version of the module size designed by the module factory. The vacuum time is 330S, the lamination temperature is 140℃, and the lamination time is 510S. After the laminated components are cooled, observe the overflow and wrinkles. The number of laminated components is 1000.

[0065] Example 1

[0066] Take a piece of transparent EVA film and a pre-crosslinked white EVA film with a size of 200mm×300mm, a piece of ultra-white embossed glass with a size of 200mm×300mm, and a white backplane with a size of 200mm×300mm, and a surface that is flat, clean, free of pollution, scratches, delamination, and bubbles. Take a TOPCon single-glass cell with a size of 182mm×182mm, and break the cell from the center. Figure 1 As shown. From bottom to top, stack the glass, transparent EVA film 1, battery cell fragments, white EVA film 2, and backplane in this order. Pay special attention to the distance between the edge of the battery cell and the edge of the glass of 10mm, as shown in the figure. Figure 2 As shown. Then put the prepared sample into the laminator, vacuum for 330 seconds, lamination temperature for 140°C, and lamination time for 510 seconds. After the laminated components are cooled, observe the overflow and wrinkles. The number of laminated components is 100.

[0067] Example 2

[0068] Take a piece of transparent EVA film with a size of 200mm×300mm and a piece of white composite co-extruded EVA film that has been pre-crosslinked, a piece of ultra-white embossed glass with a size of 200mm×300mm with a flat surface, clean and pollution-free, and a piece of white backplane with a size of 200mm×300mm with a flat surface, no pollution, no scratches, no delamination, and no bubbles. Take a piece of TOPCon single-glass cell with a size of 210mm×210mm, and break the cell from the center. Figure 1 As shown. From bottom to top, stack the glass, transparent EVA film 1, battery cell fragments, white composite co-extruded EVA film 2, and backplane in this order. Pay special attention to the distance between the edge of the battery cell and the edge of the glass of 10mm, as shown in the figure. Figure 2 As shown. Then put the prepared sample into the laminator, set the vacuum time to 330S, the lamination temperature to 140℃, and the lamination time to 510S. After the laminated components are cooled, observe the overflow and wrinkles. The number of laminated components is 100.

[0069] Example 3

[0070] Take a piece of transparent EVA film and a pre-crosslinked white EVA film with a size of 200mm×300mm, a piece of ultra-white embossed glass with a size of 200mm×300mm, and a white backplane with a size of 200mm×300mm, and a surface that is flat, clean, free of pollution, scratches, delamination, and bubbles. Take a TOPCon single-glass cell with a size of 182mm×182mm, and break the cell from the center. Figure 1 As shown. From bottom to top, stack the glass, transparent EVA film 1, battery cell fragments, white EVA film 2, and backplane in this order. Pay special attention to the distance between the edge of the battery cell and the edge of the glass of 10mm, as shown in the figure. Figure 2 As shown. Then put the prepared sample into the laminator, set the vacuum time to 330S, the lamination temperature to 140℃, and the lamination time to 510S. After the laminated components are cooled, observe the overflow and wrinkles. The number of laminated components is 1000.

[0071] Comparative Examples 1-2 use the whitening and wrinkle test methods commonly used by component manufacturers, and use standard-sized components for testing. Examples 1-3 use the whitening and wrinkle test methods provided by the present invention of breaking the battery cells. The examples and comparative examples use the same film material, backplane and glass. Table 1 shows the appearance and whitening and wrinkle ratios of the laminated parts of the examples and comparative examples.

[0072] Table 1 Lamination test results of Comparative Examples 1-2 and Examples 1-2

[0073]

[0074] Where, overflow and wrinkle rate = number of overflow and wrinkle components / total number of laminated components

[0075] By comparing the experiments using a single layer of white EVA film in Example 1 and Comparative Example 1, it can be seen that the wrinkle and white overflow rates of the test scheme provided by the present invention are similar to those of the test scheme of Comparative Example 1, and the lamination results of the composite co-extruded white film of Example 2 and Comparative Example 2 are the same, and in Comparative Example 1, Example 1 and Example 3, it can be seen that the statistical number of samples is changed, and the wrinkle and white overflow rates are very close. Therefore, the test method provided by the present invention is feasible, and the test accuracy of white overflow and wrinkles is high, which is of great help to the evaluation of early product quality.

[0076] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.

Claims

1. A photovoltaic film whitening and wrinkling test method, the steps are as follows: (1) Select transparent film, white film, glass and back panel; (2) Select a square battery cell and hit the center of the cell to break it; (3) Sample preparation: stack the glass, transparent film, cell fragments, white film and backplane in order from bottom to top and fix them; (4) Heating lamination: heating lamination is performed under vacuum to obtain a laminate sample; (5) Observe the test results: After the laminate cools down to room temperature, observe the whitening and wrinkles of the laminate.

2. The testing method according to claim 1, characterized in that: The sizes of the transparent adhesive film, the white adhesive film, the glass and the back plate are m mm×n mm, and m and n are less than or equal to 1000.

3. The testing method according to claim 1, characterized in that: The transparent adhesive film is an EVA adhesive film or an EVT adhesive film.

4. The testing method according to claim 1, characterized in that: The white film is a white EVA film, preferably a pure white EVA film or a co-extruded composite white EVA film.

5. The testing method according to claim 1, characterized in that: The backplane is a white backplane, preferably a TPC backplane.

6. The testing method according to claim 1, characterized in that: The size of the battery cell is M mm×M mm, where M is less than or equal to 800.

7. The testing method according to claim 1, characterized in that: The cell is a TOPCon single-glass cell.

8. The testing method according to claim 1, characterized in that: The battery cell was broken into four triangular fragments by being struck.

9. The testing method according to claim 1, characterized in that: During the sample preparation process of step (3), the sample is fixed with masking tape.

10. The testing method according to claim 1, characterized in that: During the heating and laminating process of step (4), the vacuuming time is 50-1000s.

11. The testing method according to claim 1, characterized in that: During the heating and lamination process in step (4), the lamination time is 300-800s.

12. The testing method according to claim 1, characterized in that: When the battery cell is knocked, dust-free paper is placed under the battery cell.

13. The testing method according to claim 1, characterized in that: During the heating and lamination process of step (4), the lamination temperature is 100-180°C.

14. The testing method according to claim 1, characterized in that: When tapping the battery cell, use a hard material such as the end of a utility knife.

15. The testing method according to claim 1, characterized in that: The distance between the edge of the cell and the edge of the glass is less than 50 mm.